Classifications of voltage stability margin (VSM) and load power margin (LPM) using probabilistic neural network (PNN) - Mohamad Nor, Ahmad Fateh; Sulaiman, Marizan; Abdul Kadir, Aida Fazliana; Omar, Rosli (Asian Research Publishing Network (ARPN), 2017)
Voltage stability margin (VSM) and load power margin (LPM) arethe indicators that show how close a load bus is to experiencing voltage instability. The smaller the values of VSM or LPM of a particular load bus, the closer the load bus towards voltage instability. This paper presents the application of probabilistic neural network (PNN) for classifying VSM and LPM values. A number of training data is generated for the PNN model to classify. The PNN model used in this paper should be able to classify which values are within VSM/LPM values and which values are not. The IEEE 14-bus system has been chosen as the reference electrical power system. MATLAB is used to deploy the PNN model for VSM and LPM classifications.